Six years of adaptive and on-farm spring cereal research in Newfoundland: Summary - Simms, Alvin; Spaner, D.; McKenzie, D. B.; Todd, A. G.; MacPherson, M.; Woodrow, E. F. (Canadian Journal of Plant Science, 2000)
Imported feed is the largest single farm operating expense in Newfoundland, yet the local production of feed grains is negligible. The federally-funded Feed Freight Assistance Program once provided annual subsidies of approximately $2 million for the transport of grain into the province, but this program was terminated in 1995. Self-sufficiency in grain production is thus a desirable long-term objective for Newfoundland livestock farmers.